Anti-hypervariable region antibody induced by a defined peptide: an approach for studying the structural correlates of idiotypes. - Chen, P P (1984)
The structural correlates of idiotypes have been sought in several antibody systems. However, the precise molecular basis of idiotypes are exceedingly difficult to define. Antibodies of predetermined specificity can be induced by immunization with synthetic peptides. In the present experiments, a synthetic peptide corresponding to a hypervariable region on a monoclonal human IgM rheumatoid factor (Sie) has been used to induce specific anti-hypervariable region antibodies. The antibodies bound to the intact Ig molecule and to its isolated heavy chains but not to other IgM paraproteins nor to pooled human IgG. The binding of the antibody to the intact IgM was inhibited specifically by the free peptide, and the antibody activity was removed by a peptide-coupled affinity column. These results clearly demonstrate that specific anti-idiotypic antibody of predefined specificity can be induced by a hypervariable region peptide. Antibodies of this class may provide a new tool for defining the structural correlates of idiotypes.